Nanoparticles for Glioblastoma Treatment - Dorota Bartusik-Aebisher; Kacper Rogóż; David Aebisher (Pharmaceutics, 2025)
GBM is the most common and aggressive primary brain tumor in adults, characterized by low survival rates, high recurrence, and resistance to conventional therapies. Traditional diagnostic and therapeutic methods remain limited due to the difficulty in permeating the blood–brain barrier (BBB), diffuse tumor cell infiltration, and tumor heterogeneity. In recent years, nano-based technologies have emerged as innovative approaches for the detection and treatment of GBM. A wide variety of nanocarriers, including dendrimers, liposomes, metallic nanoparticles, carbon nanotubes, carbon dots, extracellular vesicles, and many more demonstrate the ability to cross the BBB, precisely deliver therapeutic agents, and enhance the effects of radiotherapy and immunotherapy. Surface functionalization, peptide modification, and cell membrane coating improve the targeting capabilities of nanostructures toward GBM cells and enable the exploitation of their photothermal, magnetic, and optical properties. Furthermore, the development of miRNA nanosponge systems offers the simultaneous inhibition of multiple tumor growth mechanisms and the modulation of the immunosuppressive tumor microenvironment. This article presents current advancements in nanotechnology for GBM, with a particular focus on the characteristics and advantages of specific groups of nanoparticles, including their role in radiosensitization.